2015
DOI: 10.3109/10715762.2015.1022539
|View full text |Cite
|
Sign up to set email alerts
|

Analytical tools for the analysis of β-carotene and its degradation products

Abstract: Abstractβ-Carotene, the precursor of vitamin A, possesses pronounced radical scavenging properties. This has centered the attention on β-carotene dietary supplementation in healthcare as well as in the therapy of degenerative disorders and several cancer types. However, two intervention trials with β-carotene have revealed adverse effects on two proband groups, that is, cigarette smokers and asbestos-exposed workers. Beside other causative reasons, the detrimental effects observed have been related to the oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 196 publications
(426 reference statements)
0
32
0
5
Order By: Relevance
“…On the other hand, the lipid peroxidation assay with the β-carotene/linoleic acid co-oxidation system is an in vitro test that reproduces physiological situations of oxidative stress, which can lead to cell death in extreme cases by compounds that act on lipid environment (Alam et al, 2013;Stutz et al, 2015). Our data revealed that EEPR had an antioxidant potential against lipid peroxidation by inhibiting oxidative process and was more effective than rutin and quercetin.…”
Section: Ligandsmentioning
confidence: 69%
“…On the other hand, the lipid peroxidation assay with the β-carotene/linoleic acid co-oxidation system is an in vitro test that reproduces physiological situations of oxidative stress, which can lead to cell death in extreme cases by compounds that act on lipid environment (Alam et al, 2013;Stutz et al, 2015). Our data revealed that EEPR had an antioxidant potential against lipid peroxidation by inhibiting oxidative process and was more effective than rutin and quercetin.…”
Section: Ligandsmentioning
confidence: 69%
“…This may be attributed to the high solubility of β-carotene pigments in the powder form of herbs because grinding whole herbs affects the cell wall permeability and releases the β-carotene from the thylakoid membranes of the chloroplast. Owing to the high surface area and small particle size, the hot water extract of powder showed higher β-carotene content (Stutz, Bresgen, & Eckl, 2015).…”
Section: β-Carotene Contentmentioning
confidence: 99%
“…It is utilized as a food coloring agent (E number E160) [135] and also acts as a precursor and inactive form of vitamin A in nature (synthesized from carotenoids with the help of the enzyme β-carotene 15,150-monooxygenase). After biosynthesis, vitamin A conversion into retinoid takes place to prevent hypervitaminosis A [238,239].…”
Section: β-Carotenementioning
confidence: 99%